EFFECT OF VITAMIN D SUPPLEMENTATION ON LIPID PROFILE IN PATIENTS OF ACUTE CORONARY SYNDROME - Jabeen, Sidra; Khan, Humaira Fayyaz; Majeed, Sana; Ashfaq, Mehvish; Munir, Hina; Safder, Saira (Pakistan Journal of Physiology, 2022)
Background: Association studies have proposed a link between vitamin D levels and lipid profile. Deranged lipid profile is hallmark of acute coronary syndrome (ACS) patients. The present study was aimed to determine the role of vitamin D supplementation in improving the lipid profile of ACS patients. Methods: A total of 40 patients diagnosed with ACS were included in the study. They were divided into control (n=20) and experimental group (n=20). Experimental group received vitamin D supplementation as a single dose of 200,000 IU orally. Baseline vitamin D levels and lipid profile were done. Post sampling was done after an interval of 2 months for the same parameters. Results: The serum levels of cholesterol were decreased significantly in the experimental group (p=0.05) while TG levels showed trend towards a decrease (p=0.084). Serum HDL was increased (p=0.03), while serum LDL (p=0.04) and cholesterol ratio (p=0.012) were decreased significantly. Conclusion: Vitamin D supplementation improved lipid profile in ACS patients, and can be used as adjunct therapy in ACS patients. Pak J Physiol 2022;18(1):32?5